2008
DOI: 10.1007/s10741-008-9086-x
|View full text |Cite
|
Sign up to set email alerts
|

Iron and anemia in human biology: a review of mechanisms

Abstract: The biology of iron in relation to anemia is best understood by a review of the iron cycle, since the majority of iron for erythropoiesis is provided by iron recovered from senescent erythrocytes. In iron-deficiency anemia, storage iron declines until iron delivery to the bone marrow is insufficient for erythropoiesis. This can be monitored with clinical indicators, beginning with low plasma ferritin, followed by decreased plasma iron and transferrin saturation, and culminating in red blood cells with low-Hb c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
72
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 110 publications
0
72
0
5
Order By: Relevance
“…However, iron concentrations in body tissues must be strictly regulated because excessive iron leads to tissue damage, as a result of formation of free radicals and iron overload. Disorders of iron metabolism are among the most common diseases of humans and encompass a broad spectrum of diseases with diverse clinical manifestations, ranging from iron deficiency anemia to iron overload and, likely, to neurodegenerative diseases [1][2][3]. In healthy organism the problem of the regulation of the iron concentration has been solved by storing iron in the iron storage protein ferritin that consists of 24 protein subunits shell and nanosized ferrihydrite (5Fe 2 O 3 9H 2 O) core [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, iron concentrations in body tissues must be strictly regulated because excessive iron leads to tissue damage, as a result of formation of free radicals and iron overload. Disorders of iron metabolism are among the most common diseases of humans and encompass a broad spectrum of diseases with diverse clinical manifestations, ranging from iron deficiency anemia to iron overload and, likely, to neurodegenerative diseases [1][2][3]. In healthy organism the problem of the regulation of the iron concentration has been solved by storing iron in the iron storage protein ferritin that consists of 24 protein subunits shell and nanosized ferrihydrite (5Fe 2 O 3 9H 2 O) core [4].…”
Section: Introductionmentioning
confidence: 99%
“…In healthy organism the problem of the regulation of the iron concentration has been solved by storing iron in the iron storage protein ferritin that consists of 24 protein subunits shell and nanosized ferrihydrite (5Fe 2 O 3 9H 2 O) core [4]. The iron deficiency is a serious disease leading to anemia [1,2]. In the case of the latter iron containing medicaments are used for treatment the iron deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…This reduction in the EPO level increases the hepicidin (antimicrobial peptide produced by hepatocytes) expression which causes systemic iron deficiency and anaemia (Handelman & Levin, 2008). Another action of ACEI is the pharmacological inhibition of the renin-angiotensin system in clinical trials, which is correlated with minute but statistically significant reduction in Hb levels (Tang & Katz 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This effect on haematological parameters might be due to the depression of renin-angiotensin system by ACEIs, as this system is involved in the regulation of haematopoiesis (Cole et al 2000). This depression of renin-angiotensin system down regulates EPO which might affect the hepcidin expression and cause iron deficiency with anaemia (Handelman & Levin 2008;Liu et al 2012). In our study, the EPO-treated group showed improvement in the haematological parameters and anaemia induced by lisinopril (ACEI).…”
Section: Discussionmentioning
confidence: 99%
“…El progreso en la depleción de las reservas de este mineral se expresa como anemia, estadío final de esta carencia (9)(10)(11). Ambos estadíos, tienen similares implicaciones en el deterioro de la capacidad intelectual, desarrollo motor y la capacidad laboral (2,9,(12)(13)(14)(15).…”
unclassified